Particles for multiplexed analysis in solution: detection and identification of striped metallic particles using optical microscopy - Walton, Ian D; Norton, Scott M; Balasingham, Arjuna; He, Lin; Oviso, Jr, Dominador F; Gupta, Dimpy; Raju, Paul A; Natan, Michael J; Freeman, R Griffith (Analytical chemistry (Washington), 2002)
In this report, we present data demonstrating that cylindrical metallic particles, with various submicrometer striping patterns, may be readily distinguished in an optical microscope. Accurate particle identification is discussed relative to synthesis reproducibility and the limitations of optical microscopes. Results from a library of these particles, of which over 100 different striping patterns have been produced, are presented. For these particles, made with Au and Ag stripes, more than 70 patterns may be identified with greater than 90% accuracy. The ability to chemically modify the surface of these particles, making them useful for bioanalytical measurements, is also demonstrated. Finally, we discuss improvements in our manufacturing and identification processes that will lead to both larger numbers of striping patterns and improved identification accuracy.